FAO conservation guide; No.34 - J M Boffa (FAO, 1999)
The book reviews the status of knowledge of the traditional agroforestry systems in Sudano-Sahelian region, and synthesizes the experiences relating to the biophysical, socio-economic and policy aspects of their management.